First record of Damiria Keller, 1891 from Brazil, with the description of a new species (Poecilosclerida; Demospongiae; Porifera) - Santos, George Garcia; Pinheiro, Ulisses (Zootaxa, 2013)
Damiria Keller, 1891 is defined by possessing fistular shape with apically microspined tylotes as the only megascleres, and microscleres that may include toxas (Hooper 2002). Van Soest et al. (1994) broadened the definition of Damiria to allow the inclusion of Damiria toxifera van Soest et al., 1994, first species with toxas in the genus. These were the first microscleres assigned to the genus. Damiria is a small genus with six members widely distributed over the world’s oceans (van Soest et al. 2012): D. curvata (Vacelet, 1969) from Mediterranean Sea; D. fistulatus (Carter, 1880) from South India and Sri Lanka; D. leonorae van Soest et al., 1994 from Curaçao; D. simplex from Red Sea; D. testis Topsent, 1928 from Gorringe Bank in the South European Atlantic Shelf; and D. toxifera from Seychelles and Andaman Sea (India). Here, we are recording Damiria for Brazil for the first time and describing a new species. The specimens were collected during a faunistic survey conducted in the area of Ponta do Seixas (Paraíba State, Brazil).